2022
DOI: 10.3390/metabo12090797
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Untargeted Metabolic Profile Differentiates Children with Autism from Their Unaffected Siblings

Abstract: Autism Spectrum Disorder (ASD) encompasses a clinical spectrum of neurodevelopmental conditions that display significant heterogeneity in etiology, symptomatology, and severity. We previously compared 30 young children with idiopathic ASD and 30 unrelated typically-developing controls, detecting an imbalance in several compounds belonging mainly to the metabolism of purines, tryptophan and other amino acids, as well as compounds derived from the intestinal flora, and reduced levels of vitamins B6, B12 and foli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 61 publications
2
14
1
Order By: Relevance
“…Despite the fact that we only found nominally associated metabolites, our findings align with previously reported urine-based metabolomic studies for autism diagnosis. For instance, we observed elevated levels of phenylpyruvate (Noto et al, 2014;Timperio et al, 2022) and taurine (Ma et al, 2021;Mavel et al, 2013;Nadal-Desbarats et al, 2014;Yap et al, 2010), as noted earlier in several studies. We also show decreased levels of carnitine, similarly to what was reported in other biological samples (Fahmy et al, 2013;Filipek et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Despite the fact that we only found nominally associated metabolites, our findings align with previously reported urine-based metabolomic studies for autism diagnosis. For instance, we observed elevated levels of phenylpyruvate (Noto et al, 2014;Timperio et al, 2022) and taurine (Ma et al, 2021;Mavel et al, 2013;Nadal-Desbarats et al, 2014;Yap et al, 2010), as noted earlier in several studies. We also show decreased levels of carnitine, similarly to what was reported in other biological samples (Fahmy et al, 2013;Filipek et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…This is an important aspect to account for, when investigating suitable biomarkers in lieu of the high prevalence of co-occurring NDCs in autism (Khachadourian et al, 2023). The size of our study cohort (N=96, with n=38 diagnosed with autism) is larger when compared to several recently published studies using urine-based mass spectrometry, such as 60 available samples from an otherwise larger cohort (Liu et al, 2022), 57 participants (Mussap et al, 2020) and 14 autism discordant sibling pairs (Timperio et al, 2022). The twin cohort also gives us the possibility to analyse the effects of genetic and environmental factors on these potential biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are all considered risk factors for ASD [ 204 , 205 , 206 ]. Even though single compound changes of KP are still controversial in each clinical study ( Table 1 ) [ 1 , 2 , 8 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 ], it is clear that an abnormal balance of KP metabolites may be associated with adverse fetal neurodevelopment and the pathogenesis of ASD.…”
Section: Perinatal Kp Metabolismmentioning
confidence: 99%
“…In another urinary metabolomic study, the authors identified significant dysregulation to the purine, tyrosine, phenylalanine and tryptophan pathways, characterized by increased phenylalanine and decreased tyrosine levels. As a result of bacterial degradation, the concentrations of phenylacetic acid, phenylpyruvic acid, and 4-ethylphenyl-sulfate were also elevated [ 168 ].…”
Section: Gut Microbiota In Children and Adolescents With Asdmentioning
confidence: 99%